Pengaruh Sistem Informasi Akuntansi dan Penggunaan Teknologi Informasi Terhadap Kinerja Individu Karyawan Pada PT Fajar Abadi Mahameru - Feny Nur Rohmawati; Maria Yovita R. Pandin (Jurnal Mutiara Ilmu Akuntansi, 2023)
PT Fajar Abadi Mahameru, which is located at Jalan Kadaka No. 7A, Jatimulyo, Lowokwaru, Malang City, is a company engaged in the manufacturing sector. The phenomenon that occurs at PT Fajar Abadi Mahameru is that company assignments carried out by employees have not provided maximum performance for the company. The purpose of this research is to examine and analyze the influence of Accounting Information Systems and Information Technology Use on the performance of individual employees at PT Fajar Abadi either partially or simultaneously. This type of research is quantitative with data collection techniques using questionnaires distributed to 40 employees according to the research criteria. Based on the findings of the analysis, it can be concluded that the accounting information system and the use of information technology partially have a positive but not significant effect on the performance of individual employees. While the accounting information system and the use of information technology simultaneously (together) affect the performance of individual employees.